Karakteristik Kimia dan Mutu Organoleptik Seduhan Bubuk Kopi Liberika Pada Berbagai Metode Fermentasi dan Lama Penyangraian Biji - Marpaung, Ridawati; Nasamsir, Nasamsir; Ramadhani, Aleks (Universitas Batanghari, 2025)
The quality of Liberica coffee powder brew is influenced by the fermentation and roasting processes of coffee beans. This study aims to determine the effect of the interaction of fermentation methods and roasting duration of Liberica coffee beans on the chemical characteristics and organoleptic quality of the brew. This study was conducted in Sungai Aji, Sungai Terap Village, Betara Subdistrict, Tanjung Jabung Barat Regency (harvesting, sorting, pulping, drying, hulling, and drying), while roasting, grinding, sieving, testing the pH of ground coffee, and the organoleptic quality of ground coffee brew were carried out at the Basic Laboratory of the Faculty of Agriculture, Batanghari University, from March to August 2025.This study used a factorial completely randomized design (CRD). The first factor is the fermentation method (f) consisting of 3 levels, f0 = without fermentation; f1 = dry fermentation and f2 = wet fermentation. The second factor is the roasting duration (p), consisting of 2 levels including p1 = 20 minutes and p2 = 30 minutes. The variables observed were pH, color, aroma, taste, bitterness and preference of the brew. Data were analyzed using analysis of variance and continued with the DNMRT test at α level of 5%. The results showed no significant interaction between the fermentation method and roasting duration on pH, color, aroma and bitterness of the coffee powder brew but there was a significant interaction on the parameters of taste and preference of the coffee powder brew. The fermentation method treatment had no significant effect on the pH, color, aroma, and bitterness parameters of the brewed coffee grounds. The roasting time treatment significantly affected the pH, color, aroma, and bitterness parameters of the brewed coffee grounds. The panelists' organoleptic test results showed the highest color scores for treatments f2 (3.35) and p2 (3.53), the highest aroma scores for treatments f0 (3.55) and p2 (3.68), the highest preference score for the combination of treatments f2p2 (4.03), the highest bitterness scores for treatments f0 (3.33) and p2 (3.59), and the highest preference impression for the brewed coffee grounds using the dry fermentation method and a roasting time of 130 minutes (f2p2) with a value of 14.16.